Developmental lead exposure in rats: is a behavioral sequel extended at F2 generation? - Trombini, T. V.; Pedroso, C. G.; Ponce, D.; Almeida, A. P.; Godinho, A. F. (Elsevier B.V., 2001)
Lead toxicity was studied in rats exposed from conception until weaning and assessed by monitoring offspring behavior in both the open field and elevated plus maze and by determining tissue lead in an assessment schedule extended to first (F1) and second (F2) generations. Dams utilized for the F1 generation were submitted to 750 ppm of lead (acetate) in drinking water during pregnancy and lactation. For F1 pups, behavioral alterations were not detected in the elevated plus maze, while in the open field, spontaneous locomotor activity as well as time of both grooming and rearing increased, while freezing time decreased in 30- and 90-day-old rats. Lead content was higher in tissues of 1- and 30-day-old pups. However, in 90-day-old rats, lead was detected only in the femur. F2 generation was lead-free but still presented alterations in both locomotor activity and grooming in 30- and 90-day-old pups. It appears that developmental lead exposure may cause behavioral effects during the developmental stage of the F1 generation, which remains throughout the animal's adult life as a sequel, regardless of lead accumulation, and is extended to the F2 generation of rats. (C) 2001 Elsevier B.V. All rights reserved.
Keywords: lead; rat; behavioral assessment; development